An impedance method for spatial sensing of 3D cell constructs – towards applications in tissue engineering1. Issue 17 (7th September 2015) - Canali, C.; Mazzoni, C.; Larsen, L. B.; Heiskanen, A.; Martinsen, Ø. G.; Wolff, A.; Dufva, M.; Emnéus, J.
<x xml:space="preserve">Abstract</x> We present the characterisation and validation of multiplexed 4-terminal (4T) impedance measurements as a method for sensing the spatial location of cell aggregates within large three-dimensional (3D) gelatin scaffolds.